2020
DOI: 10.3390/w12071881
|View full text |Cite
|
Sign up to set email alerts
|

Supplied Sediment Tracking for Bridge Collapse with Large-Scale Channel Migration

Abstract: Here, we provide a numerical model that assigns an identification number to trace sediments and also identify the source of sediment supply. We analyze the efficacy of our model by reproducing the reach-scale field observations from flooding events in 2010 and 2016 that affected Kyusen Bridge over the Bebetsu River, Hokkaido, Japan. Our simulation results can successfully reproduce and trace the formation of bars caused by sediment supply in the study region. Our study also suggests a strong relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 47 publications
0
9
0
1
Order By: Relevance
“…Further, various other studies have used numerical models to understand the meandering processes and their role in the sediment supply. In this regard, Inoue et al, 2020 [ 58 ] developed used a numerical model to reproduce the flooding events of 2010 and 2016 that destroyed the Kyusen Bridge over the Bebetsu River, Hokkaido, Japan. This study further suggested a strong relationship between erosional bank rates, flow discharge, and sediment supply, as was observed in our study as well.…”
Section: Resultsmentioning
confidence: 99%
“…Further, various other studies have used numerical models to understand the meandering processes and their role in the sediment supply. In this regard, Inoue et al, 2020 [ 58 ] developed used a numerical model to reproduce the flooding events of 2010 and 2016 that destroyed the Kyusen Bridge over the Bebetsu River, Hokkaido, Japan. This study further suggested a strong relationship between erosional bank rates, flow discharge, and sediment supply, as was observed in our study as well.…”
Section: Resultsmentioning
confidence: 99%
“…96 % der beschädigten Brücken befanden sich zwischen den unteren Teilen der Bergtäler und den oberen Teilen der Schwemmfächer. Flussbette in diesen Bereichen neigen aufgrund der aus den Bergregionen antransportierten großen Mengen von Sedimenten dazu, erheblich anzusteigen [46]. Oft erfahren Leitmedien aber gar nicht von diesen Einstürzen im ländlichen Raum.…”
Section: Auswirkungen Von Brückeneinstürzen Und Berichterstattungunclassified
“…Kang et al [17] also applied this model to reproduce the experiments of Bertoldi et al [16], and demonstrated its general applicability in reproducing the braided channel. This type of morphodynamic model has been widely used to reproduce not just the braided channel but different types of large-scale morphodynamic phenomena, i.e., alternate bars [23,24], multiple bars [22], and meandering [25,26], and its use has been validated as well. These applications suggested that the model can also be applied to model several bar patterns (alternate and multiple bars) in this study.…”
Section: Flow Sediment Transort and Morphodynamics: Eulerian Approachmentioning
confidence: 99%